2001
DOI: 10.5334/ai.0511
|View full text |Cite
|
Sign up to set email alerts
|

The Volubilis project, Morocco: excavation, conservation and management planning

Abstract: Vo lubilis in northern Morocco is fam ous for th e impressive rem ains of its Roman city, but it was also an important early Islamic town and is listed by UNESCO as a World Heritage site. Te ams fr om Morocco and th e In stitute of Archaeology recently began a joint project th ere, fo cused on the investigation of the Islamic occupation and th e conservation and presentation of th e site to th e public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Specific studies on historical Morocco in the pre-Roman, Roman, and Islamic era were initiated since 1950 and continue today with several works [5][6][7][8]. All these studies revealed that the Moroccan cultural heritage is spatially distributed in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Specific studies on historical Morocco in the pre-Roman, Roman, and Islamic era were initiated since 1950 and continue today with several works [5][6][7][8]. All these studies revealed that the Moroccan cultural heritage is spatially distributed in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…assigning bakers, millers, and miller-bakers the same title. 72 Mediterranean certainly contributed to economic growth, but it still falls into the category of initial specialization and fits pre-existing notions of 'catch-up' economics and so- 78…”
Section: The Creation Of 'New Work': Sub-industries and Branch-industmentioning
confidence: 71%
“…Another inscription from the Praedia Iuliae Felicis records the rental of a bath, tabernae, and multiple cenacula over a domus. 72 simultaneously providing wealthy elites with an avenue to profit from activities in which they were not actively involved.…”
Section: Insvla Arriana Polliana (C)n Al(le)i Nigidi Mai Locantvr Ex mentioning
confidence: 99%
See 2 more Smart Citations